2020
DOI: 10.1080/14733285.2020.1755420
|View full text |Cite
|
Sign up to set email alerts
|

Not a nurse but more than a mother: the everyday geographies of mothering children with complex heath care needs

Abstract: The authors report that the study was partially funded by WellChild but that the analysis was undertaken and the paper was written independently of any oversight from WellChild. The authors gained no financial benefit from undertaking the study.Not a nurse but more than a mother: The everyday geographies of mothering children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Parenting has become an intensified task over the last decade in several ways, whether through parents' classes and workshops, "how-to" manuals, or expert advice. It has been the object of moralisation throughout history and has spawned conflicting discourses around the ideal approach to childrearing (Faircloth et al, 2013;Wilkinson et al, 2021). In the context of children's chronic disease, where we position our contribution, the extra efforts that parents of children with complex care needs have to make has been theorised as "intense parenting" (Woodgate et al, 2015).…”
Section: Readiness Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Parenting has become an intensified task over the last decade in several ways, whether through parents' classes and workshops, "how-to" manuals, or expert advice. It has been the object of moralisation throughout history and has spawned conflicting discourses around the ideal approach to childrearing (Faircloth et al, 2013;Wilkinson et al, 2021). In the context of children's chronic disease, where we position our contribution, the extra efforts that parents of children with complex care needs have to make has been theorised as "intense parenting" (Woodgate et al, 2015).…”
Section: Readiness Parentingmentioning
confidence: 99%
“…In line with the literature, our findings also suggest that the parenting approach evolves according to the emergent needs of the child (cf. Lee et al, 2014;Trnka, 2017;Wilkinson, et al, 2021), which, in the case of chronic disease, requires parents to be fully prepared for whatever emerges, and always ready to act.…”
Section: Readiness Parentingmentioning
confidence: 99%
“…Caregivers face multiple challenges in bringing up a child with a CHC, with caregiver resilience dependent, in many ways, on access to resources (Lin et al, 2013; McConnell et al, 2014). Participants displayed resilience in overcoming adversity, including social and geographical isolation through online social connections; developing knowledge of the CHC and health system; and positively reframing their caregiving and the child's CHC (Wilkinson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Children with a CHC require significantly more complex caregiving than other children (Lamar et al, 2019; Swallow et al, 2012). Mothers are compelled to balance numerous roles simultaneously; motherhood, caregiving, work and home duties, requiring resourcing for this intense labour (Wilkinson et al, 2021). Our study showed that participants acknowledged the challenges they experienced in their dual roles of caregiving and mothering (S. M. Bristow et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation